2020
DOI: 10.3390/brainsci10060331
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Gaze Patterns for Same-Race and Other-Race Faces, and the Other-Race Effect

Abstract: The other-race effect (ORE) can be described as difficulties in discriminating between faces of ethnicities other than one’s own, and can already be observed at approximately 9 months of age. Recent studies also showed that infants visually explore same-and other-race faces differently. However, it is still unclear whether infants’ looking behavior for same- and other-race faces is related to their face discrimination abilities. To investigate this question we conducted a habituation–dishabituation experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Future studies are planned to assess the generalizability of these findings to diverse populations. Such studies are particularly important in light of previous findings linking differences in gaze patterns to face stimuli of same- versus different-race 22 , 23 . Moreover, future studies will be needed to examine the specificity of the findings to autism by directly comparing blink rate and facial orientation during viewing of social and nonsocial stimuli in autistic children to that of children with other neurodevelopmental disorders, such as ADHD and language or developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are planned to assess the generalizability of these findings to diverse populations. Such studies are particularly important in light of previous findings linking differences in gaze patterns to face stimuli of same- versus different-race 22 , 23 . Moreover, future studies will be needed to examine the specificity of the findings to autism by directly comparing blink rate and facial orientation during viewing of social and nonsocial stimuli in autistic children to that of children with other neurodevelopmental disorders, such as ADHD and language or developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that the difference between our results and those reported previously are due to differences in stimuli and methodology. For example, Krasotkina et al [ 19 ] reported that White infants showed a stronger preference for eyes relative to mouths of own-race White faces than to other-race Asian faces when shown a series of static images over many habituation trials that each could be up to 40 s in duration. Similarly, Lee and colleagues found that White infants showed biases for the eyes/upper region of own-race faces and biases for mouth/lower region of other-race faces when they viewed 30 s videos of a woman counting with a neutral face [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern also might reflect infants’ attention to the mouth when exposed to more unfamiliar or difficult to process faces. For example, White infants showed a bias to prefer eyes of White own-race faces and to prefer mouths of other race Asian faces [ 19 ] or African faces [ 20 , 21 ]. Once again, however, this effect is not universal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORE develops after these perceptual preferences emerge, at approximately 9 months of age (Sangrigoli and De Schonen, 2004 ; Kelly et al, 2007 , 2009 ; Quinn et al, 2018 , 2019 ; Krasotkina et al, 2020 ; Pascalis et al, 2020 ). Foundational studies in the development of the ORE in infancy (e.g., Sangrigoli and De Schonen, 2004 ; Kelly et al, 2007 , 2009 ) have utilized a paradigm in which infants are familiarized or habituated with a stimulus and then tested for recognition of this stimulus using a visual paired comparison (VPC) including side-by-side presentations of the familiarized stimulus and a novel stimulus (Fantz, 1956 ; Fagan, 1970 ).…”
Section: Introductionmentioning
confidence: 99%